2021
DOI: 10.1007/s13311-020-00966-8
|View full text |Cite
|
Sign up to set email alerts
|

Nightmare Disorder and Isolated Sleep Paralysis

Abstract: Nightmare disorder and recurrent isolated sleep paralysis are rapid eye movement (REM) parasomnias that cause significant distress to those who suffer from them. Nightmare disorder can cause insomnia due to fear of falling asleep through dread of nightmare occurrence. Hyperarousal and impaired fear extinction are involved in nightmare generation, as well as brain areas involved in emotion regulation. Nightmare disorder is particularly frequent in psychiatric disorders and posttraumatic stress disorder. Nonmedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 45 publications
(66 reference statements)
1
36
0
Order By: Relevance
“…A five-point Likert scale is used to rate each item (e.g., 0 = no problem; 4 = very severe problem), yielding a total score ranging from 0 to 28 (21). Based on the total score the absence of insomnia (0-7); sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14); moderate insomnia (15)(16)(17)(18)(19)(20)(21); or severe insomnia (22-28) can be identified (19). Similarly, HADS is also a self-rated scale, used to assess severity of depression and anxiety symptomatology (20).…”
Section: Design Ethics and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A five-point Likert scale is used to rate each item (e.g., 0 = no problem; 4 = very severe problem), yielding a total score ranging from 0 to 28 (21). Based on the total score the absence of insomnia (0-7); sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14); moderate insomnia (15)(16)(17)(18)(19)(20)(21); or severe insomnia (22-28) can be identified (19). Similarly, HADS is also a self-rated scale, used to assess severity of depression and anxiety symptomatology (20).…”
Section: Design Ethics and Data Collectionmentioning
confidence: 99%
“…Moreover, it has been argued that the reported distress associated with parasomnia/nightmare experience may have a more significant impact on patients' quality of life, even more so than the frequency of parasomnic events [for an in-depth review of this topic please refer to (12)]. In keeping with this, to date, several psychotherapeutic approaches, for example: via Gestalt therapy (13) and imagery rehearsal therapy (14), have been shown to successfully target dysphoric parasomnias and to treat associated significant clinical distress.…”
Section: Introductionmentioning
confidence: 99%
“…Nightmare dis or der is char ac ter ized as re cur rent highly dysphoric dreams that cause dis tress and clin i cally sig nif icant mood dis tur bances, as well as so cial or cog ni tive impair ment. Such night mares are of ten a part of post-traumatic stress dis or der or other psy chi at ric comorbidity [19].…”
Section: Clin I Cal Fea Turesmentioning
confidence: 99%
“…Re ports in the sci entific lit er a ture also de scribe ob ser va tions of in creased cyclic al ter nat ing pat tern rate and hypersynchronous delta waves, de fined as con tin u ous high-volt age (>150 µV) delta waves oc cur ring dur ing slow wave sleep in cases of NREM parasomnias [21]. Sim i larly, polysomnography is not re quired for sus pected night mare dis or der or iso lated re cur rent sleep pa ral y sis, yet it is rec om mended for dif feren ti at ing them from narcolepsy or REM sleep be hav iour dis or der [19].…”
Section: Rswa Cri Te Riamentioning
confidence: 99%
“…Jalal (2018) proposes a crucial role for an increased level of the neurotransmitter serotonin when experiencing a sleep paralysis. Prior research has suggested several predisposing factors for sleep paralysis, among which sleep deprivation (Stefani and Högl 2020) and alcohol use (Munezawa et al 2011). Both sleep deprivation (Hery et al 1970;Peñalva et al 2003) and alcohol use (Chastain 2006) can increase the serotonin levels in the brain.…”
Section: Sleep Paralysismentioning
confidence: 99%